Adopted “mammoths” from Alaska turn out to be a whale's tale - Matthew J. Wooller; Pat Drukenmiller; Gonzalo Oteo‐García; Francesca Di Paolo; Love Dalén; Nick Baker; Nancy Bigelow; Stormy Fields; Sambit Ghosh; Kathryn E. Krasinski; Ben Lamm; Alistair J. Monteath; et al. (Journal of Quaternary Science, 2026)
Radiocarbon‐dated fossils indicate woolly mammoths were extirpated from mainland Beringia around 13 000 years ago. However, environmental DNA in permafrost suggests small “cryptic“ populations survived into the Holocene. Resolving this discrepancy is crucial to understanding the drivers of mammoth extinction. The Adopt‐a‐Mammoth project, launched in 2022, is increasing the number of radiocarbon‐dated mammoth fossils to locate the chronologically youngest specimens. Here, we report results from two “mammoth“ vertebral epiphyseal plates from interior Alaska that produced the youngest radiocarbon ages associated with mammoth specimens (~1900–2700 cal a BP). However, isotopic data indicated that these individuals consumed marine resources, and subsequent ancient DNA analysis revealed the specimens were in fact from a North Pacific Right whale and a Minke whale. Solving the mystery of recent “mammoth” fossils raised new questions. How did the remains of ancient whales become emplaced in sediment so far from the coastline? We briefly consider four scenarios to account for this.

Late Quaternary environmental change in eastern Beringia - Alistair J. Monteath; Mary E. Edwards; Duane Froese; Lesleigh Anderson; Benjamin V. Gaglioti; Scott L. Cocker; Julie Brigham-Grette; Matthew J. Wooller; Bruce Finney; Mark B. Abbott (Quaternary Science Reviews, 2025)

Stable isotope analyses of lacustrine chitinous invertebrate remains: Analytical advances, challenges and potential - Angela L. Lamb; Benjamin D. Barst; Clayton D. Elder; Stefan Engels; Chris Francis; Maarten van Hardenbroek; Oliver Heiri; Alex Lombino; Hannah J. Robson; Katey Walter Anthony; Matthew J. Wooller (Quaternary Science Reviews, 2024)

Highland forest dynamics across equatorial East Africa during the end of the African humid period - Sarah J. Ivory; Elizabeth MacDougal; Andrea Mason; Eleanor Pereboom; Sloane Garelick; Katherine Ficken; Matthew J. Wooller; Bob R. Nakileza; James Russell (Quaternary International, 2024)

Compound-specific stable isotopes of amino acids reveal influences of trophic level and primary production sources on mercury concentrations in fishes from the Aleutian Islands, Alaska - Michelle P. Trifari; Matthew J. Wooller; Lorrie Rea; Todd M. O'Hara; Gretchen L. Lescord; Andrew C. Parnell; Benjamin D. Barst (Science of The Total Environment, 2024)

Ecotoxicology of mercury concentrations in arctic lamprey (Lethenteron camtschaticum) - Andrew P. Cyr; Katie G. Shink; Sierra Corsetti; Andrew C. Seitz; Trent M. Sutton; J. Andrés López; Matthew J. Wooller; Todd O'Hara (Environmental Research, 2023)

BrGDGT temperature reconstruction from interior Alaska: Assessing 14,000 years of deglacial to Holocene temperature variability and potential effects on early human settlement - Jennifer R. Kielhofer; Jessica E. Tierney; Joshua D. Reuther; Ben A. Potter; Charles E. Holmes; François B. Lanoë; Julie A. Esdale; Matthew J. Wooller; Nancy H. Bigelow (Quaternary Science Reviews, 2023)

A stable isotope record of late Quaternary hydrologic change in the northwestern Brooks Range, Alaska (eastern Beringia) - Amanda L. King; Lesleigh Anderson; Mark Abbott; Mary Edwards; Matthew S. Finkenbinder; Bruce Finney; Matthew J. Wooller (Journal of Quaternary Science, 2022)
A submillennial‐resolution record of lake water oxygen isotope composition (δ 18 O) from chironomid head capsules is presented from Burial Lake, northwest Alaska. The record spans the Last Glacial Maximum (LGM; ~20–16k cal a bp ) to the present and shows a series of large lake δ 18 O shifts (~5‰). Relatively low δ 18 O values occurred during a period covering the LGM, when the lake was a shallow, closed‐basin pond. Higher values characterize deglaciation (~16–11.5k cal a bp ) when the lake was still closed but lake levels were higher. A rapid decline between ~11 and 10.5k cal a bp indicates that lake levels rose to overflowing. Lake δ 18 O values are interpreted to reflect the combined effects of changes in lake hydrology, growing season temperature and meteoric source water as well as large‐scale environmental changes impacting this site, including opening of the Bering Strait and shifts in atmospheric circulation patterns related to ice‐sheet dynamics. The results indicate significant shifts in precipitation minus evaporation across the late Pleistocene to early Holocene transition, which are consistent with temporal patterns of vegetation change and paludification. This study provides new perspectives on the paleohydrology of eastern Beringia concomitant with human migration and major turnover in megafaunal assemblages.

Ancient horse genomes reveal the timing and extent of dispersals across the Bering Land Bridge - Alisa O. Vershinina; Peter D. Heintzman; Duane G. Froese; Grant Zazula; Molly Cassatt‐Johnstone; Love Dalén; Clio Der Sarkissian; Shelby G. Dunn; Luca Ermini; Cristina Gamba; Pamela Groves; Joshua D. Kapp; et al. (Molecular Ecology, 2021)
The Bering Land Bridge (BLB) last connected Eurasia and North America during the Late Pleistocene. Although the BLB would have enabled transfers of terrestrial biota in both directions, it also acted as an ecological filter whose permeability varied considerably over time. Here we explore the possible impacts of this ecological corridor on genetic diversity within, and connectivity among, populations of a once wide‐ranging group, the caballine horses ( Equus spp.). Using a panel of 187 mitochondrial and eight nuclear genomes recovered from present‐day and extinct caballine horses sampled across the Holarctic, we found that Eurasian horse populations initially diverged from those in North America, their ancestral continent, around 1.0–0.8 million years ago. Subsequent to this split our mitochondrial DNA analysis identified two bidirectional long‐range dispersals across the BLB ~875–625 and ~200–50 thousand years ago, during the Middle and Late Pleistocene. Whole genome analysis indicated low levels of gene flow between North American and Eurasian horse populations, which probably occurred as a result of these inferred dispersals. Nonetheless, mitochondrial and nuclear diversity of caballine horse populations retained strong phylogeographical structuring. Our results suggest that barriers to gene flow, currently unidentified but possibly related to habitat distribution across Beringia or ongoing evolutionary divergence, played an important role in shaping the early genetic history of caballine horses, including the ancestors of living horses within Equus ferus .

A bio‐available strontium isoscape for eastern Beringia: a tool for tracking landscape use of Pleistocene megafauna - Juliette Funck; Clement Bataille; Jeffrey Rasic; Matthew Wooller (Journal of Quaternary Science, 2021)
Numerous paleoecological questions concern the mobility of ancient fauna in eastern Beringia. Strontium (Sr) isotope ratio ( 87 Sr/ 86 Sr) analysis has emerged as a powerful tracer for determining the provenance of ancient biological materials. However, it is important to characterize 87 Sr/ 86 Sr variation across a landscape. We measured the 87 Sr/ 86 Sr composition of teeth from present‐day, herbivorous rodents ( n = 162) sampled from across eastern Beringia to estimate bio‐available 87 Sr/ 86 Sr values. We compiled these data with the very limited number of previously published 87 Sr/ 86 Sr values from the region. We then used this dataset and a machine learning, random‐forest regression to predict bio‐available 87 Sr/ 86 Sr variations across eastern Beringia. As a case study using our new 87 Sr/ 86 Sr map (isoscape), we measured the 87 Sr/ 86 Sr and oxygen stable isotope values (δ 18 O) of five radiocarbon‐dated steppe bison from eastern Beringia and compared these to our 87 Sr/ 86 Sr isoscape and a δ 18 O isoscape to estimate the probable landscape use of these ancient fauna. Our model and isoscape provide important foundations for a wide range of additional applications, including studies of the paleo‐mobility of other fauna, ancient people and present‐day fauna in eastern Beringia.

Sources of primary production to Arctic bivalves identified using amino acid stable carbon isotope fingerprinting - Audrey G. Rowe; Katrin Iken; Arny L. Blanchard; Diane M. O'Brien; Renate Døving Osvik; Martina Uradnikova; Matthew J. Wooller (Isotopes in Environmental and Health Studies, 2019)

Synchronized proxy‐based temperature reconstructions reveal mid‐ to late Holocene climate oscillations in High Arctic Svalbard - Tomi P. Luoto; Antti E. K. Ojala; Laura Arppe; Stephen J. Brooks; Eija Kurki; Mimmi Oksman; Matthew J. Wooller; Marek Zajączkowski (Journal of Quaternary Science, 2018)
Existing paleoclimate data are exceedingly sparse from southern Spitsbergen, a High Arctic region predicted to experience significant environmental changes because of amplified warming. We analyzed biotic and isotopic paleolimnological proxies to reconstruct past climate from a lacustrine sediment core, with a basal age of ∼5500 a BP , in southern Spitsbergen (77°N). We used fossil Chironomidae assemblages to quantitatively reconstruct past mean July air temperatures and stable oxygen isotope values (δ 18 O) of these fossils to estimate changes in mean annual air temperature. These proxy records are strikingly similar and show that the coldest anomaly since the mid‐Holocene occurred between 350 and 50 cal a BP , during the ‘Little Ice Age’, whereas the warmest period in the summer temperature record occurred between 5500–5000 and ∼2000 cal a BP . Our findings indicate that the natural long‐term air temperature dynamics in our study area are most likely connected to solar minima and positive feedback mechanisms from sea‐surface temperature maxima. The results also highlight that the recent temperature increase is unprecedented in its rate with a ∼2 °C increase in the summer temperatures during the past ∼50 years.

The southern coastal Beringian land bridge: cryptic refugium or pseudorefugium for woody plants during the Last Glacial Maximum? - Yue Wang; Peter D. Heintzman; Lee Newsom; Nancy H. Bigelow; Matthew J. Wooller; Beth Shapiro; John W. Williams (Journal of Biogeography, 2017)
Aim The Bering Land Bridge ( BLB ) connected Asia and North America during glacial periods, supported a diverse ecosystem of now‐vanished megafauna, and is a proposed glacial refugium. This study tests whether southern coastal Beringia was a refugium for woody taxa during the Last Glacial Maximum ( LGM ) and hypotheses about habitats available on the BLB before and after megafaunal extinction. Location St. Paul Island, Alaska. Methods We analysed sediment cores from the Lake Hill, with a new age model anchored by 18 radiocarbon dates and multiple palaeoecological indicators (sedimentary ancient DNA [seda DNA ], macrobotanical fossils, and pollen) for the presence/absence of four woody genera: Picea, Betula, Alnus and Salix . We reconstructed vegetation history and compare St. Paul tundra composition to mainland counterparts. Results St. Paul has been continuously occupied by graminoid‐forb tundra with prostrate shrubs ( Salix , Ericaceae) since 18,000 years before present (yr bp ). Fossil pollen of Picea, Pinus, Betula and Alnus is present in the Lake Hill sediments at low relative abundances and accumulation rates, consistent with long‐distance transport. Macrobotanical fossils and seda DNA analyses do not support Picea, Betula and Alnus presence. The St. Paul modern and fossil pollen assemblages are compositionally unlike mainland counterparts, but most closely resemble Arctic herbaceous tundra. Stratigraphically constrained cluster analysis indicates no major change in the vegetation after woolly mammoth extinction at 5600 yr bp , although Poaceae, Cyperaceae, Equisetum and forb abundances increase. Main conclusions This study strongly indicates that St. Paul and, by implication, southern coastal Beringia were not refugia for woody taxa during the LGM . The persistence of prostrate shrub‐graminoid tundra supports interpretations that herbaceous tundra prevailed on southern Beringia during the LGM , whilst not ruling out the possibility of mesic shrub tundra in the interior. This herbaceous tundra supported an island refugium for woolly mammoth for 8000 years, showing no major vegetation composition changes after extinction.

Methane‐derived carbon flow through microbial communities in arctic lake sediments - Ruo He; Matthew J. Wooller; John W. Pohlman; James M. Tiedje; Mary Beth Leigh (Environmental Microbiology, 2015)
Summary Aerobic methane ( CH 4 ) oxidation mitigates CH 4 release and is a significant pathway for carbon and energy flow into aquatic food webs. Arctic lakes are responsible for an increasing proportion of global CH 4 emissions, but CH 4 assimilation into the aquatic food web in arctic lakes is poorly understood. Using stable isotope probing ( SIP ) based on phospholipid fatty acids ( PLFA‐SIP ) and DNA ( DNA‐SIP ), we tracked carbon flow quantitatively from CH 4 into sediment microorganisms from an arctic lake with an active CH 4 seepage. When 0.025 mmol CH 4 g −1 wet sediment was oxidized, approximately 15.8–32.8% of the CH 4 ‐derived carbon had been incorporated into microorganisms. This CH 4 ‐derived carbon equated to up to 5.7% of total primary production estimates for Alaskan arctic lakes. Type I methanotrophs, including Methylomonas , Methylobacter and unclassified Methylococcaceae , were most active at CH 4 oxidation in this arctic lake. With increasing distance from the active CH 4 seepage, a greater diversity of bacteria incorporated CH 4 ‐derived carbon. Actinomycetes were the most quantitatively important microorganisms involved in secondary feeding on CH 4 ‐derived carbon. These results showed that CH 4 flows through methanotrophs into the broader microbial community and that type I methanotrophs, methylotrophs and actinomycetes are important organisms involved in using CH 4 ‐derived carbon in arctic freshwater ecosystems.

Sourcing fatty acids to juvenile polar cod (Boreogadus saida) in the Beaufort Sea using compound-specific stable carbon isotope analyses - Cory Graham; Laura Oxtoby; Shiway W. Wang; Suzanne M. Budge; Matthew J. Wooller (Polar Biology, 2014)

Tracing long‐term tropical montane ecosystem change in the Eastern Arc Mountains of Tanzania - JEMMA FINCH; MATTHEW WOOLLER; ROB MARCHANT (Journal of Quaternary Science, 2014)
Pollen, charcoal, stable carbon and nitrogen isotope, and radiocarbon analyses are used to reconstruct a palaeoenvironmental record from the Eastern Arc Mountains (EAM), Tanzania, dating back >45 000 years. A sedimentary hiatus covering the last glacial‐interglacial transition (LGIT) and early to mid Holocene follows the lead up to the Last Glacial Maximum (LGM) period. A late Holocene portion of the record is included as a modern analogue. Before 45 000 cal a BP, very low regional pollen counts imply open vegetation surrounding the site. Subsequently, the development of extensive montane forest characterizes a relatively mesic pre‐LGM. The transition into the LGM witnessed a marked shift from C 3 ‐ to C 4 ‐dominated biomass, representing an expansion of open forest dominated by grasses. These changes may be attributed to a combination of enhanced moisture stress and CO 2 limitation, factors that may have been exacerbated by an intensive fire regime, as evident from the charcoal record. This is supported by a decrease in montane forest taxa, coupled with an associated expansion of C 4 graminoids and ericaceous heathland to form a montane grassland mosaic similar to that previously recorded on other East African mountains around the time of the LGM but not, to date, having been shown in the Eastern Arc Mountains.

Fatty acid and stable isotope characteristics of sea ice and pelagic particulate organic matter in the Bering Sea: tools for estimating sea ice algal contribution to Arctic food web production - Shiway W. Wang; Suzanne M. Budge; Rolf R. Gradinger; Katrin Iken; Matthew J. Wooller (Oecologia, 2014)

An ~11,200 year paleolimnological perspective for emerging archaeological findings at Quartz Lake, Alaska - Matthew J. Wooller; Joshua Kurek; Benjamin V. Gaglioti; Les C. Cwynar; Nancy Bigelow; Joshua D. Reuther; Carol Gelvin-Reymiller; John P. Smol (Journal of Paleolimnology, 2012)

Reconstruction of past methane availability in an Arctic Alaska wetland indicates climate influenced methane release during the past ~12,000 years - Matthew J. Wooller; John W. Pohlman; Benjamin V. Gaglioti; Peter Langdon; Miriam Jones; Katey M. Walter Anthony; Kevin W. Becker; Kai-Uwe Hinrichs; Marcus Elvert (Journal of Paleolimnology, 2012)

Identification of functionally active aerobic methanotrophs in sediments from an arctic lake using stable isotope probing - Ruo He; Matthew J. Wooller; John W. Pohlman; Catharine Catranis; John Quensen; James M. Tiedje; Mary Beth Leigh (Environmental Microbiology, 2012)
Summary Arctic lakes are a significant source of the greenhouse gas methane (CH 4 ), but the role that methane oxidizing bacteria (methanotrophs) play in limiting the overall CH 4 flux is poorly understood. Here, we used stable isotope probing (SIP) techniques to identify the metabolically active aerobic methanotrophs in upper sediments (0–1 cm) from an arctic lake in northern Alaska sampled during ice‐free summer conditions. The highest CH 4 oxidation potential was observed in the upper sediment (0–1 cm depth) with 1.59 µmol g wet weight −1 day −1 compared with the deeper sediment samples (1–3 cm, 3–5 cm and 5–10 cm), which exhibited CH 4 oxidation potentials below 0.4 µmol g wet weight −1 day −1 . Both type I and type II methanotrophs were directly detected in the upper sediment total communities using targeted primer sets based on 16S rRNA genes. Sequencing of 16S rRNA genes and functional genes ( pmoA and mxaF ) in the 13 C‐DNA from the upper sediment indicated that type I methanotrophs, mainly Methylobacter , Methylosoma , Methylomonas and Methylovulum miyakonense , dominated the assimilation of CH 4 . Methylotrophs, including the genera Methylophilus and/or Methylotenera, were also abundant in the 13 C‐DNA. Our results show that a diverse microbial consortium acquired carbon from CH 4 in the sediments of this arctic lake.

The detailed palaeoecology of a mid‐Wisconsinan interstadial (ca. 32 000 14 C a BP) vegetation surface from interior Alaska - Matthew J. Wooller; Grant D. Zazula; Misha. Blinnikov; Benjamin. V. Gaglioti; Nancy. H. Bigelow; Paul. Sanborn; Svetlana. Kuzmina; Catherine. La Farge (Journal of Quaternary Science, 2011)
We present a multi‐proxy reconstruction from a well‐preserved vegetation surface (ca. 32 000 14 C a BP) from the Fox Permafrost tunnel near Fairbanks, Alaska. A thick litter layer of plant material on the vegetation surface is consistent with the vegetation lacking evidence of disturbance. Plant macrofossils and graminoid cuticle analysis show the presence of a graminoid assemblage consistent with phytolith data. The pollen data indicate that trees were not local to the site and that Artemisia sp. was present in the region. The insect and bryophyte reconstructions are consistent with the vascular plant reconstruction, indicating the site was at least periodically wet. δ 13 C values from the graminoids present show a large range encompassing both the wet and dry range displayed by modern graminoids in Alaska. Sequential δ 13 C analyses conducted along the length of leaves attached to the vegetation surface indicate a seasonal shift towards relatively higher water use efficiency. The lower water use efficiency earlier in the growing season may have stemmed from the use of winter season meltwater by plants at the site – a scenario consistent with the site's cryostratigraphy. Our multi‐proxy reconstruction contributes to the limited palaeoecological data available for graminoid‐dominated vegetation present in Eastern Beringia and particularly the interior of Alaska during the mid‐Wisconsinan interstadial. Copyright © 2011 John Wiley & Sons, Ltd.

A multiple stable isotope record of Late Quaternary limnological changes and chironomid paleoecology from northeastern Iceland - Matthew Wooller; Yiming Wang; Yarrow Axford (Journal of Paleolimnology, 2008)

Towards an understanding of late Quaternary variations in the continental biogeochemical cycle of silicon: multi‐isotope and sediment‐flux data for Lake Rutundu, Mt Kenya, East Africa, since 38 ka BP - F. Alayne Street‐Perrott; Philip A. Barker; Melanie J. Leng; Hilary J. Sloane; Matthew J. Wooller; Katherine J. Ficken; David L. Swain (Journal of Quaternary Science, 2008)
Silicon is an essential nutrient for marine diatoms, which dominate the export of organic carbon to the deep ocean. Despite the dominance of the oceanic Si budget by fluvial inputs and the role of the land biosphere in controlling Si losses from rocks and soils to rivers, few studies have considered how continental bio geochemical Si fluxes varied on an orbital timescale. We reconstruct changes in Si cycling by the catchment‐lake ecosystem of Lake Rutundu, Mt Kenya (3078 m a.s.l.), over the last ca. 38 ka, using a novel combination of lake‐sediment fluxes and stable‐isotope ( δ 13 C, δ 15 N, δ 18 O, δ 30 Si) data. Under glacial conditions (38.3–14.3 ka BP), high diatom productivity was maintained by substantial losses of dissolved SiO 2 and soil nutrients from a sparse, leaky, terrestrial ecosystem. During the following period of enhanced monsoon rainfall and seasonality (14.3–9.5 ka BP), rapid Si cycling by fire‐prone, mesic grassland was associated with substantial aeolian transport of opal phytoliths by smoke plumes, but greatly reduced nutrient losses in runoff. Invasion of tall, subalpine shrubs after 9.5 ka BP further enhanced landscape stability, leading to very low sediment fluxes of both phytoliths and diatoms. This case study offers new insights into processes that may have operated at biome to continental scales during the late Quaternary. © Natural Environment Research Council (NERC) copyright 2008. Reproduced with the permission of NERC. Published by John Wiley & Sons, Ltd.

Stable isotope characteristics across narrow savanna/woodland ecotones in Wolfe Creek Meteorite Crater, Western Australia - Matthew J. Wooller; Beverly J. Johnson; Andrew Wilkie; Marilyn L. Fogel (Oecologia, 2005)

Mangrove ecosystem dynamics and elemental cycling at Twin Cays, Belize, during the Holocene - Matthew J. Wooller; Hermann Behling; Barbara J. Smallwood; Marilyn Fogel (Journal of Quaternary Science, 2004)
Existing at the transition between the terrestrial environment and hydrosphere, mangroves are sensitive to environmental change (e.g. sea‐level rise). We present pollen and stable isotope data from a core (TCC1) of continuous (10 m) mangrove peat from Twin Cays, ∼12 km off of the coast of Belize, Central America. Radiocarbon dates on fragments of mangrove leaves preserved in TCC1 show that the core provides an 8600 14 C year record of mangrove ecosystem changes. Variation in the stable carbon and nitrogen isotope composition (δ 13 C = ∼−30 to −25‰; δ 15 N = ∼−6 to 2‰) of mangrove leaves imply that the stand structure and nutrient status of the mangroves at the site have changed during the Holocene. Pollen data from the same core show that the floral composition of the site has changed at points during the Holocene, most notably a brief (∼240 years) switch at ∼3860 14 C yr BP to dominance by a species of Myrsine (not currently present at the site). Our results are consistent with significant environmental changes (either marked disturbance from hurricanes or fluctuations in sea‐level) through the Holocene. Copyright © 2004 John Wiley & Sons, Ltd.

Quantitative paleotemperature estimates from δ18O of chironomid head capsules preserved in arctic lake sediments - Matthew J. Wooller; Donna Francis; Marilyn L. Fogel; Gifford H. Miller; Ian R. Walker; Alexander P. Wolfe (Journal of Paleolimnology, 2004)

Carbon and nitrogen stable isotopic variation in Laguncularia racemosa (L.) (white mangrove) from Florida and Belize: implications for trophic level studies - Matthew Wooller; Barbara Smallwood; Myrna Jacobson; Marilyn Fogel (Hydrobiologia, 2003)